2018
DOI: 10.22452/iojel.vol2no1.4
|View full text |Cite
|
Sign up to set email alerts
|

Striving To Restrain Employee Turnover Intention Through Ethical Leadership And Pro-Social Rule Breaking

Abstract: The increased turnover intention of employees has always been a dilemma for organizations. This is not only affecting the working standards of institutions but is also depriving them of thequalified and talented workforce. Turnover intention can be represented as the movement of a person from an institution across its membership boundary. Talented, highly qualified and satisfied academicians are required for the prosperity of any higher education institution. If the academicians are not motivated and satisfied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…(3) With sustainable organizational identification as the dependent variable, the double-edged sword effect of MPSRB is analyzed and confirmed. This conclusion integrates the previous perspectives on its positive role [17,19,20] or negative role [23,24], and has important implications for the more general theoretical question of "MPSRB→employees' attitude/behavior". This provides some empirical evidence for the theoretical framework proposed by Liu and Wang [14] and Liu and Li [16].…”
Section: Theoretical Contributionssupporting
confidence: 81%
See 1 more Smart Citation
“…(3) With sustainable organizational identification as the dependent variable, the double-edged sword effect of MPSRB is analyzed and confirmed. This conclusion integrates the previous perspectives on its positive role [17,19,20] or negative role [23,24], and has important implications for the more general theoretical question of "MPSRB→employees' attitude/behavior". This provides some empirical evidence for the theoretical framework proposed by Liu and Wang [14] and Liu and Li [16].…”
Section: Theoretical Contributionssupporting
confidence: 81%
“…However, some studies have found the opposite, pointing out that the MPSRB will not only damage the interests of other group members [6], but also undermine the institution's system of organization and negatively influence employee attitudes, such as procedural justice, psychological contract, and attribution to leadership [2], which indirectly lead to negative working behaviors among employees and turnover intention [2,23] and decrease service performance [24]. Hence, MPSRB is possibly a double-edged sword for organizations, exerting positive and negative effects on employees' sustainable attitude and behavior simultaneously, thereby attracting further studies to explore their respective theoretical mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Follower becomes more tolerant with many differences, easy to accept discrepancies and the most prominent of this research, the respondents see everyone is good, including the leader. Besides, when leaders perform high-minded behavior, it will lead to a good culture which can reduce the turnover intention (Majeed, Jamshed & Mustamil, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Faculty members should proactively incorporate more effective teaching methods, change the existing dysfunctional practices such as absenteeism, late arrival, poor class engagement, etc., that are hampering teaching quality, give constructive suggestions and continuously enhance their knowledge and teaching skills. At the level of group, there must be interpersonal trust and good transactive memory allowing the faculty members in public sector HEIs in Pakistan to have awareness of the pertinent knowledge and competencies of faculty members in department with open communication (Majeed et al , 2018). All faculty members should actively communicate, suggest improvements for betterment and voice their concerns and avoid side lining able faculty members for personal gains.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%